Alterations in Electroencephalography Theta as Candidate Biomarkers of Acute Cannabis Intoxication - Richard, Christian D.; Poole, Jared R.; McConnell, Marissa; Meghdadi, Amir H.; Stevanovic-Karic, Marija; Rupp, Greg; Fink, Abigail; Schmitt, Rose; Brown, Timothy L.; Berka, Chris (Frontiers in Neuroscience, 2021)
The trend towards cannabis legalization in the United States over the past two decades has un-surprisingly been accompanied by an increase in the number of cannabis users and use patterns that potentially pose wider risks to the public like driving under the influence. As such, it is be-coming increasingly important to develop methods to accurately quantify cannabis intoxication and its associated impairments on cognitive and motor function. Electroencephalography (EEG) offers a non-invasive method for quantitatively assessing neurophysiological biomarkers of intoxication and impairment with a high degree of temporal resolution. Twelve healthy, young recreational cannabis users completed a series of neurocognitive tasks with concurrent EEG acquisition using the ABM STAT X24 EEG headset in a within-subject counterbalanced design. The one-hour testbed consisted of resting state tasks and tests of attention and memory. Spectral densities were computed for resting state tasks, and event-related potentials (ERP) were obtained for the attention and memory tasks. Theta band power (3-5 Hz) was decreased during cannabis intoxication compared to placebo during resting state tasks, as were average P400 and late positive potential (LPP) amplitudes during attention and memory tasks. Cannabis intoxication was also associated with elevated frontal coherence and diminished anterior-posterior coherence in the Theta frequency band. This work highlights the utility of EEG to identify and quantify neurophysiological biomarkers from recordings obtained during a short neurocognitive testbed as a method for profiling cannabis intoxication. These biomarkers may prove efficacious in distinguishing intoxicated from non-intoxicated individuals in lab and real-world settings.